Experimental Analysis of the Thermal Performance of a Latent Heat Energy of Helical Coil for the Application of Solar Energy. (25th January 2022) - Jayakumar, T.; Rubavathy, S. Jaanaa; Karpagam, R.; Diwakaran, S.; Jayadhas, S. Arockia; Ahamed, Maqusood; Sureshkumar, Shanmugam
Abstract : The latent thermal power storage system has more characteristics than the sensitive storage system. The heating system is a process of releasing and absorbing heat energy using phase transfer material (PCM) and it provides more efficient energy than sensible heat storage. This also consist of high energy storage and high density. It provides high heat transfer in low volume and thereby enhances heat transfer. This enhances the capacity and efficiency of the EFU while extending the service life. The coil tube is designed for latent thermal energy storage to implement and enhance thermal performance during the loading and unloading process. The offloading time, however, was not affected by the flows. Higher throughput has also been shown to improve the effectiveness of recovery. The direction of flow of the HTF did not affect the total time of loading and recharging but affected the temperature changes of the PCM in the energy storage element. It is intended to predict the ability to store maximum energy as higher energy efficiency during the phase shift process. Parameters such as the mean temperature of the PCM, the growth of the melting front, the energy efficiency, and the number of generations of entropy are studied.